2013
DOI: 10.1002/pon.3261
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐related self‐efficacy following a consultation with an oncologist

Abstract: Depression seems to be a potential risk factor for lower cancer-related self-efficacy, following an oncologist consultation. By identifying patients who exhibit symptoms of depression, health professionals can increase their attention on empowering these patients. Furthermore, our results suggest that patients' experience of self-efficacy depends on what particular challenges they have to overcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 41 publications
1
28
1
Order By: Relevance
“…In addition, patients with cancer can perceive a loss of control in their lives, which can potentially lead to debilitating psychological effects . Other groups have reported that SDM is correlated with a decrease in various psychologically detrimental symptoms, such as patient anxiety .…”
Section: Discussioncontrasting
confidence: 62%
“…In addition, patients with cancer can perceive a loss of control in their lives, which can potentially lead to debilitating psychological effects . Other groups have reported that SDM is correlated with a decrease in various psychologically detrimental symptoms, such as patient anxiety .…”
Section: Discussioncontrasting
confidence: 62%
“…Three of these found that the CBI predicted future stress or QoL outcomes [11, 13, 40]. Three studies did not find any correlation/predictor effect of coping efficacy with cancer [15, 18, 42], one found an improvement of the variable after a medical consult (mammogram) [41], one did not show/provided any information [23]. …”
Section: Resultsmentioning
confidence: 99%
“…anxiety or depression), and has been found to correlate highly with the total distress score of the longer version (r = 0.93) [24]. POMS-11 was used before and after the consultation to evaluate the immediate impact of the encounter on the patients' levels of distress.…”
Section: Questionnairesmentioning
confidence: 99%
“…2) Current level of emotional distress was assessed with the 11-item brief version of The Profile of Mood States (POMS), which has been used in previous studies [24] [25] [26]. POMS is a well-validated measure often used to measure changes in emotional state after interventions for cancer patients [27] [28] [29].…”
Section: Questionnairesmentioning
confidence: 99%